Lecturers Development Policy in Religious Higher Education and General Higher Education: Multi-Case Studies - Nurhadi, Ali; Mufarrikoh, Zainatul; Mubah, Hilmi Qosim; Susilawati, Endang Fauziyah; Indahsari, Kurniyati (JURNAL AL-TANZIM, 2023)
This study aims to analyze the development of lecturers in the fields of education, research, service, and support at IAIN Madura, Madura State Polytechnic, and Trunojoyo University Madura. This study uses a qualitative approach with a multi-site design. The results of the study show that in the field of education, PTK already has facilities that are planned but not optimal; in the context of learning assignments, PTK There is still no planning and nomination list for lecturers who will further study for the development of lecturers through training. In contrast, PTU has structured planning in providing lecture facilities, further study of lecturers and development of lecturers through training. The field of research at PTK still needs a RIP and guidelines because they are still in the final stage, while at PTU, there are RIPs and procedures, and training on research has also been carried out. In the field of service in PTK and PTU, there are guidelines, but in PTK, it has yet to be integrated with study programs; in PTK, it has been facilitated but not comprehensive, while in PTU, it has been carried out by all lecturers. In the supporting aspect, PTK and PTU have a development policy for all lecturers to carry out outside activities and a Tridharma-supporting development facility policy.